Self-assembled dithiothreitol on Au surfaces for biological applications: phospholipid bilayer formation - Creczynski Pasa, Tânia B. (2009)
Self-assembly of dithiothreitol (DTT) on Au(111) from solution deposition has been studied by X-ray photoelectron spectroscopy and electrochemical data. DTT molecules self-assemble on Au(111) in a lying-down configuration irrespective of the concentration and temperature. XPS and electrochemical data indicate a DTT surface coverage of y E 0.16 with two S-head–Au covalent bonds per DTT molecule. The DTT monolayer turns the Au surface hydrophilic enough to allow the formation of fluid dimyristoylphosphatidylcholine (DMPC) bilayer domains by vesicle fusion as revealed by "in situ" atomic force imaging. Methylene blue (MB) and flavin adenine dinucleotide (FAD) have been used as probes to study molecule transport across the bilayer.